2014
DOI: 10.3109/02770903.2014.938353
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of IL-10, IL-17F and IL-33 in patients with asthma: a case–control study

Abstract: Negative correlation between IL-10 and IL-33 levels may reflect a converse relationship between anti-inflammatory and pro-inflammatory cytokines in an individually balanced pattern. The association between IL-17F level and asthmatic phenotypes such as reduced FVC and FEV1, higher degree of sensitization, and post-bronchodilator reversibility needs further assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 59 publications
3
29
1
Order By: Relevance
“…The principal source of IL-33 in allergic disease is not fully known; however, airway epithelial cells, smooth muscle cells, and mast cells have been identified as key sources [18, 19, 37, 38]. Unlike previous reports [21, 22], we found no difference in plasma IL-33 levels between allergic asthmatics and healthy controls. This may be attributed to having underpowered comparisons due to the lack of detectable IL-33 levels in 5 subjects from each group.…”
Section: Discussioncontrasting
confidence: 56%
“…The principal source of IL-33 in allergic disease is not fully known; however, airway epithelial cells, smooth muscle cells, and mast cells have been identified as key sources [18, 19, 37, 38]. Unlike previous reports [21, 22], we found no difference in plasma IL-33 levels between allergic asthmatics and healthy controls. This may be attributed to having underpowered comparisons due to the lack of detectable IL-33 levels in 5 subjects from each group.…”
Section: Discussioncontrasting
confidence: 56%
“…IL-10, an anti-inflammatory cytokine, inhibits the production of pro-inflammatory cytokines and displays pleiotropic effects in asthma. IL-10 expression is significantly decreased in asthmatics, suggesting an important role of IL-10 in the pathogenesis of this disease (Raeiszadeh Jahromi et al, 2014). A previous study has suggested that the secretion of IL-10 was determined largely (74%) by heritable factors (Westendorp et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In asthmatic patients, increased expression of IL‐33 in the nuclei of airway epithelial cells has been demonstrated . It has also been reported that IL‐33 levels in the BALF and in the sera are higher in patients with asthma than those in healthy controls . Moreover, single nucleotide polymorphisms in IL‐33‐ST2 pathway are associated with asthma and specific wheezing phenotypes .…”
Section: Epithelial Cells and Their Cytokines In Allergic Airway Inflmentioning
confidence: 96%